On Multiplicative Magic Squares - Cilleruelo, Javier; Luca, Florian (The Electronic Journal of Combinatorics, 2010)
In this note, we give a lower bound for the distance between the maximal and minimal element in a multiplicative magic square of dimension r whose entries are distinct positive integers.